Constraint Induced Movement Therapy in Infants and Toddlers with Hemiplegic Cerebral Palsy: A Scoping Review. Issue 1 (12th January 2022) - Walker, Casey; Shierk, Angela; Roberts, Heather
Abstract: Cerebral Palsy (CP) is the leading cause of motor disability in childhood. Recent studies have investigated the effectiveness of constraint induced movement therapy (CIMT) as an early intervention for infants and toddlers with hemiplegic CP. This scoping review aims to identify current evidence for CIMT protocols for children 3 months to 5 years 11 months as well as clinical applications for practice and gaps in research. Selected databases and additional studies were searched and reviewed with 10 studies were selected for review. Results show CIMT for infants and toddlers is a feasible and effective treatment consisting of caregiver coaching, treatment in the child's typical environment, and just right activities. Future research is needed to determine the effects of different dosages in early CIMT, and the long term developmental effects throughout childhood.